แนวทางการส่งเสริมการอนุรักษ์และสืบทอดภูมิปัญญาว่าวไทย - พุฒิรุ่งโรจน์, อารีรัตน์ (วารสารวิทยบริการ มหาวิทยาลัยสงขลานครินทร์ | Academic Services Journal, Prince of Songkla University; Vol 25 No 2 (2557): Academic Services Journal, Prince of Songkla UniversityDO - 10.14456/asj-psu.2014.15, 2014)
การวิจัยครั้งนี้ใช้ระเบียบวิธีวิจัยเชิงคุณภาพ (Qualitative Research) มีวัตถุประสงค์เพื่อ 1) เพื่อศึกษาภูมิปัญญาว่าวไทย 2) เพื่อศึกษาการอนุรักษ์และสืบทอดภูมิปัญญาว่าวไทย 3) เพื่อศึกษาแนวทางการส่งเสริมการอนุรักษ์และสืบทอดภูมิปัญญาว่าวไทย โดยเลือกศึกษาภูมิปัญญาว่าวไทยวัดพระศรีอารย์ ตำบลบ้านเลือก อำเภอโพธาราม จังหวัดราชบุรี วัดสำโรง ตำบลสำโรง อำเภอนครชัยศรี จังหวัดนครปฐม เป็นพื้นที่ศึกษา ผู้ให้ข้อมูล ได้แก่ ปราชญ์ด้านภูมิปัญญาว่าวไทย ผู้ที่เล่นว่าวเป็นอาชีพ และผู้ที่มาเล่นว่าวเป็นการพักผ่อน เครื่องมือที่ใช้ในการวิจัย ได้แก่ แบบสัมภาษณ์แบบไม่มีโครงสร้างควบคู่กับการทำบันทึกภาคสนาม โดยผู้วิจัยใช้การศึกษาการวิเคราะห์เอกสาร การสังเกตแบบมีส่วนร่วม และการสัมภาษณ์แบบเจาะลึก โดยการตรวจสอบข้อมูลแบบสามเส้า (Triangulation) และทำการวิเคราะห์ข้อมูลเชิงคุณภาพ โดยการวิเคราะห์แบบอุปนัย(Analytic Induction) และการวิเคราะห์ข้อมูลแบบสร้างข้อสรุป ผลการศึกษาพบว่า ภูมิปัญญาว่าวไทย ประกอบด้วย ความรู้ทั้งทางด้านศาสตร์และศิลป์ ซึ่งแฝงด้วยคุณค่าหลากหลายด้านอันส่งผลต่อการดำเนินชีวิต แต่ด้วยท่ามกลางการเปลี่ยนแปลงของสังคมโลกเป็นสิ่งสำคัญที่ทำให้ภูมิปัญญาว่าวไทยถูกลดบทบาทลงกลายเป็นภูมิปัญญาที่ขาดผู้สืบทอด การถ่ายทอดความรู้จากรุ่นสู่รุ่นจึงขาดหายไป ขาดการได้รับความสนใจจากหน่วยงานและบุคคล เป็นผลให้การดำเนินงานการอนุรักษ์ภูมิปัญญาว่าวไทย จึงควรได้รับการสนับสนุนจากหน่วยงานภาครัฐ ภาคเอกชน ภาคประชาชน และสถานศึกษา โดยการจัดเก็บรวบรวมความรู้เรื่องว่าวมีการนำเสนอในรูปแบบต่างๆ ไม่ว่าจะเป็นหนังสือ สื่อการเรียนการสอน จัดตั้งให้มีการดำเนินงานร่วมกันในรูปแบบขององค์กร จัดตั้งแหล่งการเรียนรู้ภูมิปัญญาของชุมชน เพื่อก่อให้เกิดความตระหนักในการอนุรักษ์ร่วมกัน มีการบูรณาการเสริมสร้างหลักสูตรการเรียนรู้ภูมิปัญญาว่าวไทยในระบบการศึกษา สนับสนุนการสร้างครูภูมิปัญญาด้านว่าวไทยให้เพิ่มมากขึ้น อีกทั้งควรมีการประชาสัมพันธ์การจัดงานการละเล่นว่าวและเรื่องการจัดการเรียนรู้แลกเปลี่ยน เพื่อยกระดับภูมิปัญญาว่าวไทยให้เป็นกีฬาสากลและเป็นวัฒนธรรมโลก This research has used qualitative research method aiming to; 1) To study local wisdom and value of Thai kite, 2) To study the conservation and inheritance of Thai kites and 3) To study methods to support conservation and inheritance of local wisdom of Thai kites. The researcher has chosen Phra Sri-Arn Temple, Ban Luak sub-district, Photaram district, Ratchaburi, and Samrong Temple, Samrong sub-district, Nakhon Chaisri district, Nakhon Pathom to be the research areas in order to study the local wisdom of Thai kites. The interviewees are experts of Thai kite making, professional Thai kite players, and those who play as leisure activity. The tools used in this research are non-structured interview, as well as notes from field trips. The researcher conducted document analysis, participant observation and in-depth interview using triangulation method to cross-check the information. Then the researcher analyzed quantitative data by using analytic induction and by making summary structure. The results are as follows; The local wisdom of Thai kites is consisted of both knowledge of art and science. Its hidden values have influenced people’s life style. The main two values of Thai kites are as follows; firstly, individual personal development as those who inherited and participated in Thai kite activities learned to improve their development physically, mentally, intellectually, morally, socially, and traditionally. Secondly, personal philosophical improvement as there is hidden ideas of teaching people how to be morally and ethically a good person in accordance to the religious principles. Nevertheless, as the world is changing, the wisdom of Thai kites has been facing difficult situation due to the decrease of inheritors. The knowledge passed on from one generation to the next is also disappearing. Furthermore, there has been no real interest from any department or individuals, and the conservation is being conducted in very small circle. Therefore, the conservation of Thai kites should be supported by the government, private sectors, civil sectors as well as educational institutes. There should be a set of committees acting as an organization to maintain the wisdom and conservation, in order to gather all the knowledge of Thai kites and start up different forms of presentation such as books and educational materials.  Collaboration in form of an organization to establish a community learning center for local wisdom could be implemented. This will further raise awareness in conservation  among the people. The wisdom of Thai kites should also be included in Thai  educational system building up more support to Thai kite experts and identifying them as teachers to bring up awareness of conservation of this tradition. Apart from this, more events focusing on Thai kites could be introduced as well as holding forum to publicize and to uplift the local Thai kites to be a universal sport, and even to the international culture.